Membrane Engineering for Biogas Valorization - Brunetti, Adele; Barbieri, Giuseppe (Frontiers in Chemical Engineering, 2021)
Membrane operations now-days drive the innovative design of important separation, conversion, upgrading processes and contribute to realize the main principles of “green process engineering” being a dominant technology in various sectors. In this perspective, we propose the re-design of the traditional plants for biogas upgrading, integrating and /or replacing conventional operations with innovative membrane units. Bio-digester gas streams contain valuable products such as bio-methane, volatile organic compounds and volatile fatty acids, whose recovery has important advantages for the environment protection, energy saving and waste valorisation. Advanced membrane units can valorise the biogas by separating its various components, and driving environmental-friendly and little energivorous novel separation processes able to purse also the requirements of circular economy.